A comprehensive method for evaluating and reducing risk factors for project implementation - Al-Adwani, Bader M. S. M. (2019)
Risk analysis has been broadly used to make assessments for many business sectors. Consequently, risk-based decision-making is a dynamic practice that should be deliberated when a list of projects and restrictions are being assessed. Risk management practices are comprehensive in recognizing and evaluating all potential risks. Risk management events as well as risk evaluation assist the project managers to achieve the related risks factors and take applicable arrangements in decreasing the degree of significant risks thus give a significant contribution to a manageable enhancement. It is needed to create a technique and system to assess evaluate as well as manage risk elements effectively in advance. A questionnaire-based survey approach was chosen in the study to investigate risk factors allocated to manufacturing companies in Malaysia. Survey questions were adopted from previous works with slight amendments, pre-tested, and weighed for validity and reliability. Four key risk factors sets: project scope and organization, project management, business/financial, and operational, with 89 specified risk sources/ causes processes were considered in the model. The likelihood of occurrence of each risk factors was assessed by respondents with the use of a 5-grade Likert scale. This approach was used to quantify risk elements, and use them to estimate the overall project risk. The collected data has been analysed through SPSS. Results showed that more consideration was observed for Operational risk factors with respect to occurrence and influence. The proposed of this risk assessment model is developed based on the use of situational factors to predict project risks. As a result, a questionnaire based software was developed to fit the process of evaluation and reducing risk factors before and during implementation of projects execution phase. In this research, by suggesting a comprehensive risk based decision making model, the effective agents of resource impact in the process of risk identification, plan and control during financial global crisis have be identified and also identification of the effective criteria and sub-criteria in each of the identified agents. The software with a high ability of modelling and analyzing risks of the projects which is most suitable for industrial application was developed. The method, was be ready to use by the industrial practitioners for the successful completion of their projects, and also indirectly improves manufacturing project management practices, and as a result minimizes losses and increases profitability.